ANALISA FAKTOR PENYEBAB DAN AKIBAT PERUBAHAN KONTRAK PEKERJAAN (CONTRACT CHANGE ORDER) PADA PROYEK PEMBANGUNAN GEDUNG INSTALASI RAWAT INAP 2 RSUD MAREN Hi. NOHO RENUAT KOTA TUA - Lestaluhu, Damayanti; Saleh, La Mohammat; Titaley, Henriette Dorothy (Jurusan Teknik Sipil, 2024)
Construction projects often encounter problems such as changes occurring during implementation. These changes may occur in the early, middle, or late stages of the project. Hanna AS (2002) defines a change or change order (CO) in a construction project as an event leading to a change. In this study, the author uses the SmartPLS 4.0 application for data analysis techniques. SmartPLS 4.0 has an outer model/measurement model and an inner model/structural model to test the degree of validity and reliability of the indicators of the variables used in the study and also to determine the impact of relationships between each variable used in the study. Loading factor values for each indicator exceeded 0.6 and AVE values for each variable exceeded 0.5 in the convergence validity test of this study. For the discriminant validity tests, the cross-loading score and the Fornell-Larcker score meet the SmartPLS 4.0 requirements, and the HTMT score for each variable is less than 0.9. The R² test (r-squared) gave an R² value of ≥ 0.75 (75%). On the other hand, the path coefficient test yields a significance value (P-value) for the effect between variables of 0.05 or less for an alpha value of 5%. It can be said that the variables used in this study are valid and there are strong relationships between the test variables.